Indonesia Dampak Tayangan Talkshow Televisi Indonesia Lawyers Club (ILC) Terhadap Mahasiswa : (Survei Terhadap Mahasiswa Fakultas Ilmu Komunikasi dan Bahasa UBSI Margonda Depok) - Fauziah Muslimah; Eni Saeni (Jurnal Public Relations (J-PR), 2020)
The world of television broadcasting is a world of creativity. The tight competition in the television industry requires television station managers to devote brilliant ideas and ideas to maximize their creative and innovative power in producing broadcast programs. Television stations, especially commercial television, will go out of business, go bankrupt, if they fail to produce and choose programs that are attractive to the audience. The main difficulty for television station program managers is determining whether a program will reach a large audience. One of the television programs that the audience is interested in is a talk show. One of the talk show programs that can be said is phenomenal, namely "Indonesia Lawyer Club" (ILC) which aired on TV One. First broadcast in 2008, ILC is different from other talk show programs because of the number of speakers presented. The talk show hosted by a senior journalist, Karni Ilias, deviated from the "standard" talk show, featuring dozens of sources. This research focuses on the impact of the ILC program on students of the Faculty of Communication and Language at UBSI Margonda, Depok. This study uses Gerbner's Cultivation Theory, which highlights the cumulative effect of television and ultimately forms a new reality according to the reality image displayed by television. That is, we perceive the world in which we live according to the image displayed on television. In other words, cultivation theory emphasizes the very strong influence of television on the formation of public perceptions which in turn gives birth to social construction. The approach used in this research is a quantitative approach. This approach aims to explain, predict and control social phenomena through objective measurement and numerical analysis through numbers. This study uses a descriptive type with a quantitative approach in which the researcher provides a description or description of a situation as clearly as possible without any treatment of the object under study. The results of the analysis showed that there were students' affective and cognitive impacts from the ILC broadcast on TV One.